2019
DOI: 10.4103/ijmr.ijmr_97_18
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation in chronic tension-type headache: A pilot study

Abstract: Background & objectives:Tension-type headache (TTH) is the most common type of primary headache disorder. Its chronic form is often the most ignored and challenging to treat. Transcranial magnetic stimulation (TMS) is a novel technique in the treatment of chronic pain. The aim of this pilot study was to explore the effect of low-frequency repetitive TMS (rTMS) on pain status in chronic TTH (CTTH) by subjective and objective pain assessment.Methods:Patients (n=30) diagnosed with CTTH were randomized into rTMS (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…Articles that were excluded in the full-text screening are summarized in online Supplementary Table S3. Twenty-two interventional trials on the effects of BTX-A on CTTH met eligibility and were included (3960). The studies collectively exposed 652 patients with CTTH to BTX-A.…”
Section: Resultsmentioning
confidence: 99%
“…Articles that were excluded in the full-text screening are summarized in online Supplementary Table S3. Twenty-two interventional trials on the effects of BTX-A on CTTH met eligibility and were included (3960). The studies collectively exposed 652 patients with CTTH to BTX-A.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies exclusively examined patients with a disorder, ie, fibromyalgia (FM), 5,82 chronic low back pain, 14 chronic whiplash–associated disorders, 79 diabetic neuropathy, 63 chronic tension–type headache, 55 and multiple sclerosis (MS). 8 Study participants were healthy adults in 27 studies.…”
Section: Resultsmentioning
confidence: 99%
“…8 Three studies showed that rTMS induced a significant NFR inhibition in patient populations. Indeed, rTMS over the DLPFC increased the NFR threshold in patients with chronic tension-type headache and FM, 55,82 and rTMS over the M1 decreased the NFR area in patients with diabetic neuropathy. 63 Remarkably, the study in FM patients was not able to demonstrate inhibitory effects on other NFR parameters (ie, latency, duration, and amplitude).…”
Section: Noninvasive Neuromodulationmentioning
confidence: 96%
See 2 more Smart Citations